Malpractice in paediatric minimally invasive surgery – a current concept: Results of an international survey. (October 2017) - Esposito, Ciro; Escolino, Maria; Bailez, Marcela; Rothenberg, Steve; Davenport, Mark; Saxena, Amulya; Caldamone, Anthony; Szavay, Philipp; Philippe, Paul; Till, Holger; Montupet, Philippe; Holcomb 3rd, George W.
This study aimed to assess malpractice in paediatric minimally invasive surgery (MIS), and attitudes, prevention strategies and mechanisms to support surgeons while they are under investigation. An observational, multicentric, questionnaire-based study was conducted. The survey questionnaire was sent via mail, and it comprised four sections. Twenty-four paediatric surgeons (average age 54.6 years), from 13 different countries, participated in this study. The majority had >15 years of experience in MIS. Three (12.5%) surgeons reported a total of five malpractice claims regarding their MIS activity. The reasons for the claims were a postoperative complication in 3/5 (60%) cases, a delayed/failed diagnosis in 1/5 (20%) cases and the death of the patient in 1/5 (20%) cases. The claims concluded with the absolution of the surgeon in all cases, and monetary compensation to the claimant in two (40%) cases. Eleven (45.8%) surgeons were invited as expert counsels in medico-legal actions. Medico-legal aspects have a minimal impact on the MIS activity of paediatric surgeons. In this series, claims concluded with the absolution of the surgeon in all cases, but they had a negative effect on the surgeon's reputation and finances. A key element in supporting surgeons while they are under investigation is always to choose a surgeon who is an expert in paediatric MIS as legal counsel. A constant update on innovations in paediatric MIS and appropriate professional liability insurance may also play a key role in reducing medico-legal consequences.